2022
DOI: 10.1111/srt.13139
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of basal cell carcinoma by high‐resolution ultrasound elastography

Abstract: The aim of this study was to assess the value of high-resolution ultrasonic quantitative parameters of shear wave elastography (SWE) in basal cell carcinoma (BCC). A total of 86 cases of BCC were enrolled as the case group, and 38 other similar skin pigmented lesions were randomly selected as the control group. Using pathological results as the gold standard, the diagnostic test method was used to evaluate the ability of high-frequency ultrasonic elastography to diagnose BCC, and the 2D ultrasonographic featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“… 4 However, trichoscopy cannot visualize deeper skin structures such as hair follicles. 5 , 6 Ultrasonography has been widely used in dermatology for diagnosis and efficacy assessment of conditions, such as melanocytic nevi, 7 hidradenitis suppurativa, 8 basal cell carcinoma, 9 and many others. High‐frequency ultrasonography can also visualize the structure of hair follicles within the skin layer, 10 , 11 allowing observation of parameters such as the number, width, and depth of hair follicles.…”
Section: Introductionmentioning
confidence: 99%
“… 4 However, trichoscopy cannot visualize deeper skin structures such as hair follicles. 5 , 6 Ultrasonography has been widely used in dermatology for diagnosis and efficacy assessment of conditions, such as melanocytic nevi, 7 hidradenitis suppurativa, 8 basal cell carcinoma, 9 and many others. High‐frequency ultrasonography can also visualize the structure of hair follicles within the skin layer, 10 , 11 allowing observation of parameters such as the number, width, and depth of hair follicles.…”
Section: Introductionmentioning
confidence: 99%
“…It is an ultrasonic technology used to evaluate the hardness and elasticity of biological tissues. Recently, an increasing number of studies have reported that UE is highly sensitive and specific for differentiating benign and malignant tumors and it is a potential effective method for diagnosing BC [5,6].…”
Section: Introductionmentioning
confidence: 99%